2020
DOI: 10.1038/s41598-020-78563-0
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment based on multivariate statistics and water quality index of a strategic river in the Brazilian Atlantic Forest

Abstract: Fifty-four water samples were collected between July and December 2019 at nine monitoring stations and fifteen parameters were analysed to provide an updated diagnosis of the Piabanha River water quality. Further, forty years of monitoring were analysed, including government data and previous research projects. A georeferenced database was also built containing water management data. The Water Quality Index from the National Sanitation Foundation (WQINSF) was calculated using two datasets and showed an improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 80 publications
0
19
0
3
Order By: Relevance
“…The combination of a WQI and MSTs may be useful for determining the water quality of rivers. MSTs such as cluster analysis (CA), stepwise discriminant analysis (DA), principal component analysis (PCA), factor analysis (FA), co-occurrence network analysis, and Mann-Kendall trend analysis are widely used for evaluating and interpreting both temporal and spatial variations in large and complex water quality datasets, as well as for source apportionment of pollution [1,3,6,8,9,[24][25][26][27][28]. Mann-Kendall trend analysis has been applied to observe longterm patterns of water quality parameters [29].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of a WQI and MSTs may be useful for determining the water quality of rivers. MSTs such as cluster analysis (CA), stepwise discriminant analysis (DA), principal component analysis (PCA), factor analysis (FA), co-occurrence network analysis, and Mann-Kendall trend analysis are widely used for evaluating and interpreting both temporal and spatial variations in large and complex water quality datasets, as well as for source apportionment of pollution [1,3,6,8,9,[24][25][26][27][28]. Mann-Kendall trend analysis has been applied to observe longterm patterns of water quality parameters [29].…”
Section: Introductionmentioning
confidence: 99%
“…The three samples were collected for all the 5 tanks during summer, winter and monsoon seasons in the year 2020 -2021 and to observe the change in the quality of water at different timings based on the wastewater generation and wastewater flow into the tanks in the study area as well as the time of high concentration from the remote point to the sampling point. The seasons are well defined through basin and the rainfall management has balance in its distribution [7]. The samples were sealed and transferred to the laboratory and the analysis were carried out by using standard APHA procedures [8].…”
Section: Methodsmentioning
confidence: 99%
“…Twoway ANOVA test results showed that interaction effects of any variables (Akbulut et al2010). 4.PCA showed the parameters contributing for the water quality from the [7].…”
Section: Anova Analysis Based On Tanksmentioning
confidence: 99%
“…Taking China for illustration, there were 874 records of local water contamination during 2006 ~ 2016, resulting in great troubles for domestic life and making millions of economic loss 5 . Reasonable evaluation of water quality variation has been demonstrated as a practical tool for water quality warning and protection 6 8 .…”
Section: Introductionmentioning
confidence: 99%